URGENSI SAKSI VERBALISAN DALAM PERKARA TINDAK PIDANA (STUDI PUTUSAN NOMOR. 329/Pid.B/2020/PN Dgl) - Wahid, Abdul; Junaedi, Abdullah (Fakultas Hukum Universitas Muhammadiyah Palu, 2022)
The problem that will be described in this research is how is the urgency of verbal witness in criminal cases (study of decision number 329/Pid.B/2020/PN Dgl). In obtaining legal materials, this research was carried out by conducting library research with a normative juridical approach by studying the laws and regulations and analyzing the urgency of verbal witnesses in criminal cases. The answer found in the problem is that the role of verbal witnesses in providing information before the trial is only to clarify the minutes of the investigation they have made and refute the testimony of witnesses before the trial basically does not provide evidence strength in the form of witness evidence or the judge's belief in seeking material truth as the basis for judge's considerations. in making a decision. Whereas normatively verbal witnesses are not regulated in the Criminal Procedure Code, but the practice of using verbal witnesses in the process of proving a crime in court is allowed, due to the denial or revocation of testimony by witnesses at trial. Thus, the role of the verbal witness is to test the witness's rebuttal to the truth of the Investigation Report.